(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
This study aims to examine the implementation of a teaching module based on the TPACK (Technological Pedagogical and Content Knowledge) approach in the learning of tembang macapat at SMK Negeri 1 Kaligondang, Purbalingga. The focus of this research is to enhance students’ understanding, interest, and skills through the integration of technology in learning, in line with the principles of the Merdeka Curriculum, which emphasizes the development of 21st-century skills: critical thinking, creativity, communication, and collaboration. This research employs a qualitative descriptive approach, with research subjects including the principal, Javanese language teacher, and students of SMK Negeri 1 Kaligondang. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and verification. The results of the study show a significant improvement in students’ learning outcomes, with a 64.5% increase in pretest scores after the learning process. Furthermore, the implementation of the teaching module based on the TPACK approach also enhanced teachers’ creativity and innovation in designing more engaging and relevant lessons, while motivating students to be more active in the learning process. Thus, the implementation of the teaching module using the TPACK approach proves to be effective in improving learning outcomes and the quality of tembang macapat instruction, as well as supporting the creation of a more adaptive and responsive learning environment in the face of technological developments and the educational demands of the 21st century.